Analysis of Organizational and Family Roles in the Work-Life Balance of Blue-Collar Employees - Banik, Subrata; Akter, Kaniz Marium; Hoque, Md. Rashedul; Sultana, Farha (Universitas Syiah Kuala, 2024)
Objective Blue-collar workers' work-life balance (WLB) issues have not received enough attention in the literature. This study aimed to examine the impact of organizational support and family support on blue-collar employees work-life balance.Design/Methodology Employees engaged in the RMG industry in Bangladesh were surveyed using a questionnaire. 387 responses were analyzed through the PLS-SEM approach. The instrument and data were validated by a measurement model, and the hypotheses were tested by a structural model using SmartPLS 3.0 software.Results The study revealed that firm support and home support can significantly influence work-life balance, and firm support can strongly impact an employee's home life. These findings indicated that the policies and practices of RMG companies and support from family members can help employees manage their overall life smoothly.Research limitations/implications - The study was conducted in the RMG industry, which limits the generalizability of its findings. Findings suggested that by introducing employee-friendly corporate policies and human resource practices, RMG companies can assist their employees in solving work-life issues and meeting their personal and family life challenges.Novelty/Originality This study, for the first time, empirically validated firm support as an antecedent of home support. In addition, the WLB issues of blue-collar employees are focused on in this study, which has been overlooked in the prior studies.